Market Changes in the Energy and Green Energy Sector During the COVID-19 Crisis: A Global Perspective - Cristian Paun; Radu Musetescu; Valentin Cojanu; Radu Simandan (Amfiteatru Economic, 2023)
The objective of this study was to examine the effects of the COVID-19 pandemic on the energy and electricity industry, with a particular focus on green energy sources such as wind and solar energy. The analysis provided a global perspective, based on a panel of 45 countries that represent more than 90% of the world's GDP. The analysis was structured in two steps: a counterfactual analysis based on the mean and variance of the country data sample for the 14 indicators and the 45 countries in the panel and a counterfactual analysis that looked at the statistical significance of the difference of mean between the data sets referring to the time of the pandemic and before the time of the pandemic using the t-student test of 2 samples assuming unequal variances between samples. For the pandemic time, the analysis took into consideration two years (2020 and 2021), and the benchmark year was 2019. The counterfactual analysis included a short-term perspective based on a comparative analysis with the dynamic of the year before the crisis (2019/2018 dynamic) and a long-term perspective based on a comparative analysis with the multiannual average dynamic (2019/2015 – 5 years). The study results indicated that the COVID-19 pandemic has led to a decline in global energy and electricity production, a partial reduction in global greenhouse gas emissions, a partial improvement in the global trade balance with energy and electricity, a decrease in global energy and electricity consumption, and a partial increase in global green energy and electricity production and intensity.
Keywords: F01; N70; Q01; Q58; 330; COVID-19 crisis; global economy; energy; green energy; sustainable development.